2004
DOI: 10.1038/modpathol.3800101
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression and molecular abnormalities of cell-cycle-regulatory proteins in rhabdomyosarcoma

Abstract: Rhabdomyosarcoma is the most commonly occurring soft-tissue sarcoma in children. Some reports have discussed the altered expression and molecular abnormalities of cell-cycle-regulatory proteins in rhabdomyosarcoma; however, variable frequencies of occurrence have been noted. In the current study, among 72 cases of rhabdomyosarcoma, the authors evaluated for the expression of p53, MDM2, p16, p21/WAF1, p27, cyclin D1, cyclin E, pRb and E2F-1 protein immunohistochemically and assessed for proliferative activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 27 publications
(48 reference statements)
2
58
1
1
Order By: Relevance
“…[23][24][25][26][27][28][29][30] Musella et al demonstrated that cyclin D1 overexpression was an independent factor for survival in patients with sarcoma, 11 and their results were confirmed in other reports. 13,31,32 Although some investigators have demonstrated an inverse correlation between p53 immunopositivity and survival in patients with sarcoma, 9,[33][34][35] more have demonstrated that p53 has no association with patient prognosis. 13,23,26,[36][37][38][39] In the current study, clinical follow-up data on the patients with sarcoma was insufficient to establish a meaningful correlation between clinical outcome and Ig expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25][26][27][28][29][30] Musella et al demonstrated that cyclin D1 overexpression was an independent factor for survival in patients with sarcoma, 11 and their results were confirmed in other reports. 13,31,32 Although some investigators have demonstrated an inverse correlation between p53 immunopositivity and survival in patients with sarcoma, 9,[33][34][35] more have demonstrated that p53 has no association with patient prognosis. 13,23,26,[36][37][38][39] In the current study, clinical follow-up data on the patients with sarcoma was insufficient to establish a meaningful correlation between clinical outcome and Ig expression.…”
Section: Discussionmentioning
confidence: 99%
“…13,31,32 Although some investigators have demonstrated an inverse correlation between p53 immunopositivity and survival in patients with sarcoma, 9,[33][34][35] more have demonstrated that p53 has no association with patient prognosis. 13,23,26,[36][37][38][39] In the current study, clinical follow-up data on the patients with sarcoma was insufficient to establish a meaningful correlation between clinical outcome and Ig expression. However, because Igj expression correlated well with the LI of PCNA, Ki-67, and cyclin D1, it is reasonable to suggest that Ig expression also will correlate with patient clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated the loss of wild-type HRAS with retention of the activated HRAS allele in a patient with recurrent biphasic ERMS/fibrosarcoma. Interestingly, HRAS mutations are rarely seen in sporadic rhabdomyosarcoma [Yoo and Robinson, 1999;Takahashi et al, 2004] implicating an alternate mechanism of rhabdomyosarcogenesis in patients with CS.…”
Section: Discussionmentioning
confidence: 99%
“…Given that dysregulation of cell-cycle machinery has variable tumor specificity, it follows that elevated levels of CDK4 and MDM2 proteins can be detected by immunohistochemistry in a number of sarcoma types. [9][10][11][25][26][27] Interestingly, however, recent reports suggest that these markers are also useful to distinguish some poorly differentiated sarcomas from dedifferentiated liposarcoma. 7,8 We recognize that the histologic evidence of a well-differentiated component is the so-called 'gold standard' for the diagnosis of dedifferentiated liposarcoma.…”
Section: Discussionmentioning
confidence: 99%